A let's go travel guide - Torres, Andrew M.; Ebersold, Lucy B.; Carmon, Irin; Sebastia'n Andre's Brown; Hur, Angela Mi Young (London, UK : Macmillan, 2003, 2003)
The 2003 editions see a complete relaunch of this travel series - new packaging, format, and content features aimed at travellers who want more immersion in the places they're visiting, better and more in-depth factual information, and a range of exciting destinations.
"Written by Let's Go Publications"--Taken from the verso of the title page. "A Let's Go travel guide"--Cover.
TOU
Keywords: Spain -- Guidebooks; Portugal -- Guidebooks; Morocco -- Guidebooks